Isolation and Phenotypic Identification of Mycotoxigenic Fungi from Stored Maize Kernels within Dutsin–Ma Metropolis, Katsina State - Salihu, Ibrahim Salihu; Musbau, Kilani Adetunji; Abdullahi, Kamala; Bakori, Hafsat Sagir; Aliyu, Abdul Nasir; Shehu, Sani Ahmad; Wata, Innocent John (Sahel Journal of Life Sciences FUDMA, 2024)
One of the most important effects of post-harvest decay or seed deterioration by fungi is the production of mycotoxins. Mycotoxicosis is a disease of animals and humans following consumption of feeds and foods contaminated by fungi that produce toxic substances called mycotoxins. The study investigated the cultural morphology, microscopic identification, pathogenicity, and mycotoxin production of fungal isolates from 25 stored maize samples collected. Standard microbiological techniques were employed for the analysis of all the samples, Cultural morphology on Potatoes Dextrose Agar revealed diverse colony characteristics, ranging from olive and dark green hues with smooth or spongy surfaces to brownish-pink and dull yellow-green colonies. Microscopic analysis identified six different fungal species, with Aspergillus spp being the most prevalent (72%) and Mucor spp as the least prevalent (6%). Pathogenicity tests on fresh maize demonstrated that all the isolates were pathogenic, causing observable growth on the maize samples. Furthermore, mycotoxin production by the fungal was revealed by evidence of fluorescence under UV radiation, indicating the potential production of aflatoxins. Stored maize kernels from the study area were at risk of fungal attack due to poor storage facilities, poor handling practices and inadequate drying of the grains, which enabled the fungi to grow and produce mycotoxins. Therefore, farmers should be sensitized on the possible risk of fungal attack on grains and be educated on timely harvest, hygienic drying and storage practices of grains.